ENSURING ENVIRONMENTAL SAFETY OF OPERATION OF HYDROCARBON FUEL COMPONENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This scientific and analytical information presents the results on ensuring the environmental safety of the combustion process and afterburning of hydrocarbon fuel mixtures in a closed system. The results of catalytic additional oxidation of products of incomplete combustion of hydrocarbons and them oxygenates are presented. If in numerous works the use of catalysts and / or catalytic systems was put forward to prevent the formation of incomplete combustion products and their emissions into the atmosphere.And in this work, the use of a homogeneous catalyst is put forward, which ensures complete combustion of hydrocarbon fuel in the combustion chambers, which has a positive effect on the increase in engine power per unit of fuel consumption.